Role of Cholinergic Innervation and RGS2 in Atrial Arrhythmia - JONES, DOUGLAS L.; Tuomi, Jari M.; Chidiac, Peter (Frontiers in Physiology, 2012)
The heart receives sympathetic and parasympathetic efferent innervation as well as the ability to process information internally via an intrinsic cardiac autonomic nervous system (ICANS). For over a century, the role of the parasympathetics via vagal acetylcholine release was related to controlling primarily heart rate. Although in the late 1800s shown to play a role in atrial arrhythmia, the myocardium took precedence from the mid-1950s until in the last decade a resurgence of interest in the autonomics along with signaling cascades, regulators, and ion channels. Originally ignored as being benign and thus untreated, recent emphasis has focused on atrial arrhythmia as atrial fibrillation (AF) is the most common arrhythmia seen by the general practitioner. It is now recognized to have significant mortality and morbidity due to resultant stroke and heart failure. With the aging population, there will be an unprecedented increased burden on health care resources. Although it has been known for more than half a century that cholinergic stimulation can initiate AF, the classical concept focused on the M2 receptor and its signaling cascade including RGS4, as these had been shown to have predominant effects on nodal function (heart rate and conduction block) as well as contractility. However, recent evidence suggests that the M3 receptor may also playa role in initiation and perpetuation of AF and thus RGS2, a putative regulator of the M3 receptor, may be a target for therapeutic intervention. Mice lacking RGS2 (RGS2−/−), were found to have significantly altered electrophysiological atrial responses and were more susceptible to electrically induced AF. Vagally induced or programmed stimulation-induced AF could be blocked by the selective M3R antagonist, darifenacin. These results suggest a potential surgical target (ICANS) and pharmacological targets (M3R, RGS2) for the management of AF.